Fluid inclusion studies of the copper-bearing quartz veins in Gowuch Formation, Drosh-Shishi area, Chitral, northern Pakistan - Tahirkheli, Tazeem; Shah, Mohammad Tahir; Khan, Tahseenullah; Khan, Mohammad Asif (Journal of Himalayan Earth Sciences, 1996)
Copper mineralization, generally confined to the Gowuch Formation, in Drosh-Shishi area is a part of the upper crust of Kohistan arc terrain in Chitral, northern Pakistan. It is related to the hydrothermal activity and is mainly associated with altered diorites and quartz veins. It occurs in different forms; within quartz veins, along foliation planes, in dissemination and as supergene enrichment. Fluid inclusion studies indicate that the salinity of the hydrothermal solution is 12.28-13.40 equivalent wt% NaCl and the homogenization temperature ranges from 160 to 350oC. This suggests that the copper mineralization is related to the late stage vein formation as a result of diorite and granodiorite intrusion